Influence of Polymer Flexible Joint on Concrete Beams in Three-Point Bending Test - ZDANOWICZ, Łukasz; KWIECIEŃ, Arkadiusz (Engineering Transactions, 2015)
Problem of three-point bending test for concrete beam with polymer flexible joint is described in this paper. The aim of this work is to present selected potential applications of flexible joint for concrete structures. The results of experimental researches for concrete beams before failure and after repairing with flexible joint method are presented. Behaviour of members repaired (bonded) with flexible joint is analysed in comparison to the test results of concrete beam before failure. Attention is paid to beneficial, due to a higher load capacity, stress redistribution in repaired element. Numerical finite element (FE) analysis of influence of polymer flexible joint on the behaviour of elements is conducted. Stresses concentration with their redistribution and displacement pattern are presented. In conclusion, beneficial influence of application of polymer flexible joints as a method of repairing concrete elements is highlighted. Furthermore, their potential applications in concrete structures are specified.